Integrasi Teori Behavioral Dalam Edukasi Kesehatan Untuk Perubahan Perilaku Pada Sekolah Tinggi Kesehatan Mataram - Muhammad Riza; Made Sutajaya (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Introduction: Effective counseling plays a crucial role in addressing student diversity and supporting their psychological and social development within a multicultural context. Objective: This research aims to develop a multicultural counseling model based on local wisdom to improve students' self-confidence and social skills. Method: This study used a quasi-experimental design with intervention and control groups. The intervention group received counseling based on the developed multicultural model, while the control group received standard counseling. Data were collected through questionnaires and observations, and analyzed using paired t-tests to evaluate the effectiveness of the intervention. Results: The results showed that the multicultural counseling model significantly increased students' self-confidence and social skills, with statistical tests indicating a significant difference (p < 0.05) between the intervention and control groups. Conclusion: The multicultural counseling model based on local wisdom effectively enhances students' self-confidence and social aspects. This model is recommended for broader application in educational settings to support holistic student development.